Market Day and Entrepreneurial Career Development for Early Childhood - Rahayu, Watik; Munadi, Muhammad (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the implementation of the market in the context of establishing entrepreneurial careers in early childhood at Aisyiyah Kindergarten Kartasura Branch (TK ACK). The research method uses qualitative phenomenological research case studies. The subjects of the study are teachers and students of ACK Kindergarten. The research informants were the principal, parents of students and the management of Aisyiyah Kartasura Branch. The data collection tool uses participatory observations, in-depth interviews, and document studies. The data validity technique uses triangulation of sources and methods. The data analysis technique uses an interactive analysis model. The results of the study show that the market day is in accordance with the internal spirit of the affiliate and in accordance with the vision, mission and goals of the institution. Parents' participation in setting up stands for children to sell merchandise. Students make their own items that will be sold on the minus one day of implementation. The implementation of selling students by practicing by writing down the type of products sold and the price with the help of parents, students practice price bargaining, and calculate returns and income from buying and selling. The skills that appear in Market Day can strengthen the mastery of 21st century skills: : Communication skills, Creativity, Collaboration, Social skills, Literacy skills, Social responsibility, Innovation skills dan Thinking skills.